2017
DOI: 10.1016/j.conctc.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of race and ethnicity on becoming a human subject: Factors associated with participation in research

Abstract: INRODUCTION The purpose of this study was to explore factors associated with willingness of African Americans and Latinos to participate in biomedical and public health research and to delineate factors that influences the decision to become a human subject. METHODS We present results from a 2010 random digit-dial telephone survey of 2,455 African American (N= 1,191) and Latino (N= 1,264) adults. We used standard measures to assess knowledge of research, terminology, informed consent procedures, previous par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 35 publications
2
38
1
Order By: Relevance
“…Further, these studies [12,13] indicate that limited health literacy and minimal disease education contribute to the lack of enrollment of minorities into clinical trials. A recent study by Garza et al [14] looked at willingness of minorities (African American and Hispanics) to participate in clinical studies. The study was a random telephone survey, and findings suggest that respondents' top priorities for deciding to participate in the study were helping others, helping themselves, and gaining more knowledge about their disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, these studies [12,13] indicate that limited health literacy and minimal disease education contribute to the lack of enrollment of minorities into clinical trials. A recent study by Garza et al [14] looked at willingness of minorities (African American and Hispanics) to participate in clinical studies. The study was a random telephone survey, and findings suggest that respondents' top priorities for deciding to participate in the study were helping others, helping themselves, and gaining more knowledge about their disease.…”
Section: Introductionmentioning
confidence: 99%
“…This study not only demonstrated the willingness of African Americans to participate in clinical research, but also whether they were satisfied with their experience, willing to participate in future studies, and would also recommend a friend or family member. A recent study by Garza et al [14], using a population composed completely of minorities, reported that African Americans and Latinos were not only willing to participate in research but also 50% of the African Americans and 53% of the Latinos were willing to take medicine as part of a research study. These findings are contrary to perceptions on lack of participation and unwillingness of African Americans to participate in clinical trials [2,12].…”
mentioning
confidence: 99%
“…These concerns may be exacerbated among minority racial/ethnic populations who are already excessively surveilled and disproportionately diagnosed with psychiatric conditions (Grimm, ; Kreag, ; Sabatello & Appelbaum, ). Finally, underrepresentation of minority populations in genomic research may be due to far simpler reasons: studies suggest that although the interest in genomic research participation among minority groups may be high, they are too often not being asked to participate (Garza et al, ; Hartz et al, ; Millon Underwood, Buseh, Kelber, Stevens, & Townsend, ; Wendler et al, ).…”
Section: Psychiatric Genetics In Research Settingsmentioning
confidence: 99%
“…At times, the published findings do not articulate details on the influence of compensation. For example,Garza et al (2017) explored the willingness of African Americans and Latinos to participate in research and the factors that influenced their decision. However, the details related to the importance of the identified motivation factors were not included in the publication.…”
mentioning
confidence: 99%
“…Garza et al, (2017);Grady et al, (2017);Simon et al, (2011);Perez et al, (2016);Chin et al, (2015);Devine et al, (2015);Edelblute & Fisher, (2015) Application to other scenariosGrady, et al, (2017);Simon et al, (2011);Perez et al, (2016). ;Devine, et al, (2015) DependabilityDetailed description of methodsGarza, et al, (2017); Grady, et al, (2017); Simon, et al, (2011); Perez et al, (2016); Chin et al, (2015); Devine et al, ., (2017); Grady et al, (2017); Simon et al,. (2011); Perez et al, (2016); Chin et al, (2015); Devine et al,…”
mentioning
confidence: 99%